1984
DOI: 10.1111/j.1745-6584.1984.tb01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Ion, Humic Materials, and Trihalomethane Potential in Northeastern Kansas Ground Waters

Abstract: Glacial buried‐valley aquifers serve as primary sources of potable ground water in northeastern Kansas. A long known problem, however, is that a large percentage of well waters in this region exceed the U.S. Environmental Protection Agency (EPA) limits for nitrate (NO−3). A detailed study of the hydrogeology and water quality of the buried valleys has confirmed the nitrate problem and led to a recognition that some well waters with low ( 5 mg/l) NO−3 concentrations have anomalous ( 0.5 mg/l) ammonium ion (NH+4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Both NH4+ and N03" are common contaminants that result from pollution caused by fertilizer application and disposal of human and animal wastes (1-8). Dissolved NH4+ can cause taste, odor, and health problems in drinking water supplies (9), and dissolved N03~c an cause methemoglobinemia in infants at concentrations >10 mg/L as N (10). The fate of NH4+ and N03~i n groundwater is largely determined by the microbiology and geochemistry of the subsurface (11).…”
Section: Introductionmentioning
confidence: 99%
“…Both NH4+ and N03" are common contaminants that result from pollution caused by fertilizer application and disposal of human and animal wastes (1-8). Dissolved NH4+ can cause taste, odor, and health problems in drinking water supplies (9), and dissolved N03~c an cause methemoglobinemia in infants at concentrations >10 mg/L as N (10). The fate of NH4+ and N03~i n groundwater is largely determined by the microbiology and geochemistry of the subsurface (11).…”
Section: Introductionmentioning
confidence: 99%
“…Simpkins and Parkin (1993) and Parkin and Simpkins (1995) observed unusually high concentrations of dissolved organic carbon (up to 54 mg/L) in till and loess in central Iowa, which they attributed to degradation of complex organic material (i.e., wood) disseminated in the glacial materials. Denne et al (1984) and Denne et al (1987) studied glacial buried-valley aquifers in northeastern Kansas and found concentrations of TOC from 0.9 to 2.4 mg/L derived from buried humic materials sufficient to sustain relatively high ammonium concentrations (0.5 to 4.2 mg/ L). Larson and Roy (2000) traced high ammonium concentrations in portions of Illinois to the organic-rich, buried Sangamon Geosol developed on Wisconsinan-age deposits.…”
Section: Resultsmentioning
confidence: 99%
“…In Kansas, Denne et al (1987) observed an extremely strong correlation of high extractable ammonium concentrations measured in interbedded silty clay layers with high ammonium concentrations detected in the adjacent buried channel aquifer. Extractable ammonium concentrations ranged up to 75 kg/kg in the glacial sediments (Denne et al, 1984). In a point-source study of contaminated wastewater discharge into a sandy aquifer, sorbed ammonium represented a large portion of the total nitrogen load in the aquifer and an available pool of ammonium to be released to the aquifer should equilibrium conditions change (DeSimone and Howes, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In, contrast, ammonium inhibits the reaction by competing for reaction sites on the organic material (Denne et al, 1984). It may also react directly with chlorine, reducing the concentrations available to react with the organic matter.…”
Section: Ammoniummentioning
confidence: 99%
“…This results in a high bromine incorporation into the THMs and may account for the mutagenic activity of chlorinated waters which cannot be solely ascribed to chloroform (Peters, 1994). However the presence of ammonia at concentrations as low as 1 mg l -1 inhibits haloform formation by competing for reaction sites on the organic molecules (Denne, 1984). Ammonia is generally present at low concentrations in unpolluted groundwater, but is high in domestic wastewater and can be high in landfill leachates (Robinson, 1996;Stuart & Klinck, 1998).…”
Section: Trihalomethane Formationmentioning
confidence: 99%